Finite Groups of Order p2qr in which the Number of Elements of Maximal Order Is p3q∗ - Qingliang Zhang; Liang Xu (Journal of Mathematics)
Let G be a finite group. We know that the order of G and the number of elements of maximal order in G are closely related to the structure of G. This topic involves Thompson’s conjecture. In this paper, we classify the finite groups of order p2qr in which the number of elements of maximal order is p3q, where p<q<r are different primes.